(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
Information and communications technology and the rapid developments that the global economy is witnessing are in the process of growing its role in all economic journals. Accordingly, it is considered one of the most important transformation processes in the twenty-first century, as the technology sector has become the unified language of the peoples of the world, and is the main base through which their dealings begin. In addition, it raised its level, progress, and development, and to keep pace with the sequence of time that reduced the time gap. The importance of the research lies in the important role played by informatics in all economic journals, especially in transforming investment from its traditional nature to investments of an innovative nature that protects modernity and is based primarily on knowledge and human capital (highly and medium-skilled individuals), after the traditional nature was based on Muscular effort, machine power, and raw materials as raw materials in the production process. However, in light of the spread of technology and information and in light of the information society, economic power has become mainly based on knowledge, not muscle effort, and this is what was confirmed by the theory of internal growth by economist Romer. Technology is an internal variable in the production function. This in turn leads to an increase in the state’s public revenues and GDP growth. The research reached a number of conclusions, the most important of which was that the digital economy has the full ability to maximize the returns from the technology of the scientific and information revolution, to carry out all tasks, and to ensure participation in events and activities that were not available under the traditional economy. The study concluded with a set of recommendations, the most important of which was paying attention to the digital economy because it has the full ability to maximize the returns from the technology of the scientific and information revolution, to carry out all tasks, and to ensure participation in events and activities that were not available under the traditional economy.